Institutional Capacity Strengthening of the Tourism Village in Kawali Village, Kawali Subdistrict, Ciamis Regency - Shifa Zahratuni salsabila; Ela Nurlaela; Fika Febriani; Ikhtia Faizatuz Zahrah; Fina; Dio Alif fadilla; Rhagiel Latuconsina; Muhammad dzulfan Gymnastiar; Rifqi Maulana; Azra Keanu Prakudia (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Kawali Village in Kawali District, Ciamis Regency, has great potential as a tourism village based on history, culture, culinary, and the creative economy. The existence of the Astana Gede site as a legacy of the Sunda Galuh Kingdom, Kampung Nila, the Ki Bawong Cultural Studio, and creative economic activities in four hamlets are the main attractions of the tourism village. However, the management of this potential still faces various challenges, especially in the institutional aspects, human resources, and coordination between destination managers. This study aims to analyze the institutional conditions of Kawali Tourism Village and formulate strategies to strengthen institutional capacity to support integrated and sustainable tourism village management. The method used is a descriptive qualitative approach through field observations, coordination, and discussions with tourism managers, the village government, and the local community. The results show that tourism destination management is still partial, not yet integrated within a single tourism village management institution, and supported by limited human resource capacity and funding. This condition has an impact on less than optimal promotion, tourism services, and the development of integrated tourism packages. The discussion emphasized that institutional strengthening through the establishment of a tourism village management body, increasing human resource capacity, utilizing information technology, and strengthening cross-sectoral collaboration networks are key to the development of Kawali Tourism Village. In conclusion, strengthening institutional capacity is a crucial pillar in realizing an integrated, competitive, and sustainable Kawali Tourism Village. Therefore, a joint commitment between the village government, the community, and other stakeholders is required to support the optimal implementation of tourism village management. Keywords: Institutions, Tourism Village, Tourism Management.